2006
DOI: 10.1186/1477-7819-4-39
|View full text |Cite
|
Sign up to set email alerts
|

Tactile-like corpuscles in gastric mucosa: a case report

Abstract: Background: The presence of tactile corpuscle-like structures in Schwannomas, Neurofibromas and Neuroid Intradermal Melanocytic Nevi is well-documented. We report a case describing the presence of such structures in the lamina propria of grossly normal gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…7 It was found to be associated with some peripheral nerve sheath tumors, namely, traumatic neuroma, neurofibroma, neurilemmoma, and melanocytic nevi. 7 Interestingly, Fellegara et al reported an ovarian mature cystic teratoma with florid vascular proliferation and Wagner-Meissner-like corpuscles. 8 In the colon, De Beca et al observed a Schwann cell hamartoma with tactoid body features presented endoscopically as a polyp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 It was found to be associated with some peripheral nerve sheath tumors, namely, traumatic neuroma, neurofibroma, neurilemmoma, and melanocytic nevi. 7 Interestingly, Fellegara et al reported an ovarian mature cystic teratoma with florid vascular proliferation and Wagner-Meissner-like corpuscles. 8 In the colon, De Beca et al observed a Schwann cell hamartoma with tactoid body features presented endoscopically as a polyp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been named with different descriptive names, including tactoid bodies, Wagner-Meissner-like corpuscles, Pacinian corpuscles-like structures, and pseudomeissnerian corpuscles. 7 It was found to be associated with some peripheral nerve sheath tumors, namely, traumatic neuroma, neurofibroma, neurilemmoma, and melanocytic nevi. 7 Interestingly, Fellegara et al reported an ovarian mature cystic teratoma with florid vascular proliferation and Wagner-Meissner-like corpuscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCLBs have also been described in the literature as Wagner-Meissner-like corpuscles, Wagner-Meissner bodies, pseudo-Meissner corpuscles, and Meissneroid corpuscles [ 2 ]. The gastrointestinal (GI) tract is normally devoid of TCLB and, if present, they are rare findings, mostly found on incidental GI endoscopies [ 3 , 4 ]. They are believed to be reparative neural proliferation and are deemed benign with an excellent prognosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A tumor with TCLB in its entirety has also been reported in the periaortic tissue, extremities, and vulva [ 3 ]. A TCLB-associated GI tumor is unusual and almost always an incidental finding [ 3 , 4 ]. When present, they appear as spindle cells in the lamina propria [ 5 ].…”
Section: Introductionmentioning
confidence: 99%